HAY-PLASTIC COMPOSITES – EFFECT OF HAY PARTICLE SIZE ON THE WATER ABSORPTION - Križan, Peter; Matúš, Miloš; Beniak, Juraj (International Journal of Research -GRANTHAALAYAH, 2022)
The main aim of this paper is to present the research findings which come out from the experimental determination of the influence of input raw material properties and composition on the water absorption of hay-plastic composites (HPC). During the HPCs production, important raw material parameters such as hay sawdust particle size, hay/plastic concentration ratio or type of plastic matrix can be recognized. In this research study, the aim was to produce HPCs of an acceptable and competitive level of quality which is determined from the final mechanical properties of HPCs. Particle size of hay sawdust used for production of HPC has significant influence on mechanical properties of composites and also on other important properties (water absorption, hardness, frost resistance, etc.). The paper deals with the determination of the impact and the relationship between the input hay sawdust particles sizes, hay/plastic concentration ratio and water absorption of composites. By side intention of authors is to determine the possibilities of waste raw materials usage. The experimental research findings were obtained using a semi-operational injection molding press where the injection is provided by a working screw. As the input raw material, meadow hay, HDPE plastic matrix and recycled HDPE, represented by lids from PET bottles, was used. The effect of the input hay sawdust particle size on water absorption was determined according to a combination and default levels of hay/HDPE concentration ratio, using recycled HDPE instead of virgin HDPE and particle size of hay sawdust.